Keterlibatan Orang Tua dalam Pendidikan Anak Usia Dini di Satuan PAUD Islam - Agung Hidayatulloh, M.; Laily Fauziyah, Nur (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2020)
This paper describes the parental involvement in Islamic Early Childhood Education (ECE) units. The subjects of this study were parents and teachers in two Radlatul Athfal (RA). Through observation, interviews, and documentation, it is found that there are three types of parental involvement in education i.e. direct involvement in RA, direct involvement outside RA, and involvement at home. Another form of involvement is involvement that is directly requested by RA and some that are voluntary. The driving force for parental involvement in general is a form of cooperation in advancing children’s education and maintaining optimal child development. Parental involvement strategies include school production, outing, and home visits. Regarding the parental involvement model, there are two models in RA Mathla'ul Anwar, namely the protective model and the consumer model. Meanwhile, in RA Islamiyah Talun there are five models, namely the protective, transmission, curriculum-enrichment, consumer, and partnership models.